See You on the Other Side: A Novel Exploring Dissociative Identity Disorder - Laurensius Richard (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
Dissociative identity disorder (DID) is a disease in which people experience multiple separate personalities and function independently of one another and autonomously from one another. DID is a rare disease found in only 1.5% of people worldwide, so I want to find out what the cause of people having DID and how they recover from DID. The method that I will use is to create a creative work in the form of a novel. The story will involve family dysfunction and post-traumatic avoidance as the causes of DID and three approaches, which are safety and stability, work on traumatic memories, and re-integration into life, to weaken the DID effects. Narrative-wise, this creative fiction novel is set in 2022's America, where this story will highlight Ethan's daily life as the person that has DID, which creates a new identity, Elliot. The finding is that Ethan's DID effect cannot be cured, but it can be recovered with the help of Maydeline using the three approaches of DID treatment.